The Phenomenon of Punishment at Pesantren in South Sulawesi: An Islamic Law and Islamic Education Approaches - Damopolii, Muljono; Shabir U, Muhammad; Burga, Muhammad Alqadri (Islamic Family Law Department, Sharia and Law Faculty, Universitas Islam Negeri Ar-Raniry, 2023)
Pesantren (Islamic boarding school) is an educational institution in Indonesia that instills Islamic values in its students. In pesantren, the punishment given to students aims not to hurt, but to contain educational values. This study aims to analyze the application of punishment in pesantren. This research is qualitative with Islamic law and Islamic education approaches. The informants comprised several teachers and students of Pondok Pesantren DDI Mangkoso, South Sulawesi, Indonesia. Data were collected through observation, interview, and documentation, then analyzed using the descriptive analysis technique. The results showed that the forms of punishment applied to Islamic boarding schools were reprimands, assignments, and psychological and physical punishments. Punishment in Islamic boarding schools includes ta‘zīr in Islamic law. Even though there are written rules, in some cases, the implementation of ta‘zīr is very simple (depending on the subjectivity of the kiai or teacher), so it lacks legal certainty and only aims to give a deterrent effect to perpetrators. According to Islamic education, the punishments applied by Islamic boarding schools have met the objectives of implementing educational sanctions, namely a deterrent effect for the perpetrators and a deterrent for others. Therefore, legal certainty is not the main goal in determining and implementing punishment in Islamic boarding schools, but to improve the students’ scientific and moral quality. This research has implications for teacher innovation and various methods in Islamic boarding school education so that students participate in the educational process willingly and happily, not because they are forced or afraid of punishment.